Couples Coping Together: A Scoping Review of the Quantitative and Qualitative Evidence and Conceptual Work Across Three Decades - Weitkamp, Katharina; Bodenmann, Guy (Frontiers in Psychology, 2022)
Dyadic coping (DC), how couples cope together to deal with a stressor like chronic illness, has received increased attention over the last three decades. The aim of the current study was to summarize the current state of research on DC in couples. We conducted a scoping review of qualitative, quantitative, and mixed-methods studies published between 1990 and 2020, assessing dyadic coping (DC) in couples during three decades. 5,705 studies were identified in three electronic databases and hand searches. We included 643 sources in this review (with a total of N=112,923 study participants). Most studies were based in the global North, particularly in the US and Europe. Publication numbers increased constantly over time. A third of study designs were cross-sectional studies followed by qualitative and longitudinal studies. The most prolific DC research areas were related to DC and daily hassles and DC and major physical health stressors. Overall, DC has been established internationally as a highly relevant construct in many disciplines (clinical, social, developmental, personality psychology, social work, nursing etc.). To conclude, the review reveals that future studies should focus on predictors, trajectories, and the importance of very specific DC behaviors for personal and dyadic functioning.